Isolation of Quorum Sensing Inhibitory compounds from cyanobacteria - Macho, Markéta (Jihočeská univerzita, 2020)
Overuse of antibiotics has led to the development of resistance in many medically relevant human pathogens, posing a threat to human health. The recent decline in the discovery of novel antibiotics together with development of multi-antibiotic resistant strains demands a search of an alternative approach. Anti-virulence therapy poses significantly lower pressure on developing resistance given its focus on disarming the pathogen rather than eradicating it. Advancement in the field of bacterial cell-to-cell communication (Quorum Sensing, QS) and its molecular mechanism regulating the production of virulence factors in many clinically relevant human pathogens led to the discovery of Quorum Sensing inhibitory (QSI) molecules. Cyanobacteria are recognized as a prolific source of natural bioactive compounds with great pharmacological potential. The aim of this study was to screen cyanobacterial extracts for QSI activity in search of potential anti-virulence drugs. 45 cyanobacterial strains were randomly selected from the in-house culture collection of Centre Algatech, extracted, and fractionated to generate 1575 fractions for QSI evaluation. Strains 3, 16, and 113 exhibited the highest inhibitory potential against both used biosensors, E. coli pSB401 and E. coli pSB1075. The obtained results open a future prospect to isolate and elucidate the lead molecule responsible for QSI activity.
Isolation of Quorum Sensing Inhibitory compounds from cyanobacteria
Keywords: Cyanobacteria; Quorum sensing inhibition; Antimicrobial resistance; Anti-virulence therapy; Anti-microbial activity; Hemolytic activity